The Influences on Activity-Based Costing Adoption as An Optimal Costing System Design: Evidence from Saudi Arabia - Abdulrahman Aljabr (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: Under which conditions is the adoption of activity-based costing (ABC) beneficial to the business-unit and, hence, represents the optimal costing system design (CSD)? Motivation - Identifying the situations under which ABC is beneficial with regard to the performance of the business-unit and, thus, represents the optimal CSD is important in order to make a correct decision to invest in ABC. This necessitates the adoption of the matching form of fit when examining the relationship between the influential factors and ABC adoption as an optimal CSD due to its ability to reflect when ABC is beneficial and, therefore, indicate the optimal CSD. This study builds on Ittner et al. (2002) to examine this relationship from the standpoint of the matching form of fit, and also extends this line of research by examining the effect of the most key influential factors, using a sufficiently comprehensive multi-dimensional production complexity (PC) measure. Idea - This paper examines the role of the key influential factors on ABC adoption as an optimal CSD from the standpoint of the matching form of fit, using a sufficiently comprehensive multi-dimensional PC measure. Data - The data were collected from 200 Saudi manufacturing business-units. Tools - The questionnaire survey strategy was used to collect the data, which were then analysed using the residual analysis (RA) technique. Findings - Unexpectedly, the results of the RA showed that none of the examined key factors of competition, indirect costs, PC and information technology quality (IT quality) affects ABC adoption as an optimal CSD from the viewpoint of the matching form of fit. Contribution - This research contributes to the ABC adoption research by examining the situations under which ABC is beneficial and, hence, represents the optimal CSD through examining the impact of the key influential factors on ABC adoption as an optimal CSD from the standpoint of the matching form of fit.
Keywords: M41; 650; optimal costing system design (CSD); activity-based costing (ABC); contingency theory; matching form of fit; residual analysis